Effect Of Ethanol Extract Of Nutmeg Leaves (Myristica Fragrans) On Hispathotic Features Of Diabetic Rats (Ratus Norvegicus) - Latuamury, Rokia; Batmomolin, Pia; Niwele, Amelia (Bantayang Omni Cendekia, 2024)
Background: Nutmeg leaves (Myristica fragrans) are used by the community to treat some diseases such as pain. Chemicals contained in nutmeg leaves such as saponins, polyphenols, flavanoids, and essential oils. To prove the activity of ethanol extract of nutmeg leaves (myristica fragrans) against the aorta of diabetic rats (rattus norvegicus). Objective: To prove the activity of nutmeg leaf ethanol extract (myristica fragrans) against the aorta of diabetic rats (rattus norvegicus), and prove the activity of nutmeg leaf ethanol extract (myristica fragrans) on hispathological features of foam cells and aortic diameter of diabetic rats (rattus norvegicus). Methods: This research is a type of research that is laboratory experiments (laboratory experiments) in vivo using experimental animals of white rats (rattus norvegicus) male wistar strains. Results: Nutmeg leaves use 96% ethanol solvent. Maceration results of 300 g were obtained, concentrated with a rotary evaporator device obtained a thick extract of 42.673 g with a soaking % of 14.23%. Histological images were obtained of thinner and wider diameter lumen and foam cells in the tunica intima and aortic media of mice. Conclusion: From the results of research on the effect of ethanol extract of nutmeg leaves (myristica fragrans) on the hispathotic picture of aortic rats (rattus norvegicus) diabetes. To prove the activity of ethanol extract of nutmeg leaves (myristica fragrans) on hispathological features of foam cells and aortic diameter of diabetic rats (rattus norvegicus).